(untitled) (Research, Society and Development, 2023)
Orbital fractures are common in facial trauma. The identification of a lesion involving any wall of the orbit must be preceded by a good history, physical examination and complementary imaging tests. The orbital fracture that involves the orbital floor is called Blow Out and occurs due to the increase in orbital pressure by the soft tissues resulting from blunt trauma, generating the “explosion” of the orbital floor and depression of the orbital contents into the maxillary sinus. This study aimed to report a clinical case of an adolescent victim of physical aggression resulting in a Blow Out orbital fracture. This is a male patient, 15 years old, presenting pain in the left orbital region, enophthalmos and diplopia in the eye. left. The Waters radiography and computed tomography revealed herniation of the orbital fat into the maxillary sinus, which was compatible with the type of orbital fracture. It was concluded that knowledge of the indications and contraindications for defining conservative treatment or surgical treatment is of paramount importance, in order to avoid an unfavorable prognosis for the patient or subjecting him to surgical procedures with serious risks of complications, without due care. recommendation.